Evaluación de riesgos laborales para el montaje de la planta de Agregados Áridos Loma Alta. propuesta de un plan de seguridad para la prevención de riesgos laborales - Guerrero Urriola, Dennys Fernando (2021)
In this research, the evaluation of the occupational risks in the construction works for the assembly of the Loma Alta Aggregates Plant in the Daule Canton, Guayas province, is carried out, which will allow the elaboration of a Safety Plan for the prevention of occupational risks. . The investigation begins based on the results of a previous exploratory study that demonstrates the increase in demand for high-quality aggregates for the construction industry in the province, as well as the low availability of aggregate quarries in the province. market, both due to the legality of its opening and productive operations and the gradual closure of the quarries on the road to the Coast, as well as the occupational risks in the improvised quarries of the market, which by maintaining low safety standards cause an increase in the accident rate and even fatalities for workers in this industry.